AA147 ameliorates post-cardiac arrest cerebral ischemia/reperfusion injury through the co-regulation of the ATF6 and Nrf2 signaling pathways - Yuan, Zhu; Lu, Liping; Lian, Yingtao; Zhao, Yuanrui; Tang, Tingting; Xu, Song; Yao, Zhun; Yu, Zhui (Frontiers in Pharmacology, 2022)
Ischemia/reperfusion caused by cardiac arrest (CA) disturbs endoplasmic reticulum (ER) homeostasis in neurons. AA147 is a novel compound able to selectively activate the activating transcription factor 6 (ATF6) pathway, one adaptive branch of the unfolded protein response (UPR) in response to endoplasmic reticulum (ER) stress. The ATF6 pathway protects multiple tissues from ischemia/reperfusion injury (IRI) by decreasing reactive oxygen species and restoring ER function. However, it is unclear whether pharmacologic activation of the ATF6 pathway by AA147 ameliorates post-cardiac arrest cerebral IRI and whether it is associated with the anti-oxidative stress mechanism. In the present study, mice were subjected to 9 min-CA surgery followed by resuscitation. AA147 or vehicle was administered 24 hours before the operation and 15 minutes after the restoration of spontaneous circulation. We found that the expression of ATF6 and its regulated gene GRP78 increased significantly after the administration of AA147, suggesting the activation of the ATF6 pathway. AA147 restored neurological function and reduced dead neurons in mice suffering from cardiac arrest. Mechanistically, activation of ATF6 via AA147 inhibited CA/CPR-caused neuronal apoptosis and ER stress, indicated by reduced TUNEL positive neurons, surged expression of Bcl-2/Bax, and down expression of cleaved caspase-3, caspase-12, C/EBP-homologous (CHOP). In addition, AA147 also alleviated the upsurge of the ROS generation and MDA levels as well as increased SOD activity, accompanied by enhancement of Nrf2 and its modulated HO-1 expressions. The results suggested that AA147-induced activation of ATF6 could confer neuroprotection against post-cardiac arrest cerebral IRI through inhibition of oxidative stress along with ER stress-mediated apoptosis, which is partly attributed to the upregulation of the Nrf2/HO-1 signaling pathway. Our findings support the potential of activating ATF6 via AA147 as a therapeutic approach to improve CA outcomes.